Concurrent training and intermittent fasting reduce transverse cross-sectional area of cardiomyocytes and body mass in Wistar rats - Henrique Izaias Marcelo; Henrique Izaias Marcelo; Marina Politi Okoshi; Letícia Estevam Engel; Wanderson da Silva Rosa; Paulo Henrique Aleixo; Paulo Henrique Aleixo; Guilherme Akio Tamura Ozaki; Everton Alex Carvalho Zanuto; Luiz Carlos Marques Vanderlei; Francis Lopes Pacagnelli; Francis Lopes Pacagnelli; et al. (Frontiers in Physiology)
MethodsThis study identified the alterations caused by concurrent training and intermittent fasting on the myocardium of rats. In total, 39 adult male Wistar rats were used, divided into four groups: control [C (n = 12)], fasting control [FC (n = 11)], training [T (n = 8)], and fasting training [FT (n = 8)]. The critical load test was performed to evaluate and determine the intensity of effort in aerobic training (AT) (swimming). The resistance training protocol (RT) (anaerobic) consisted of four series of 10 jumps, with overload corresponding to 50% of the body mass of each animal, and 1 min of rest between each series. The concurrent training (CT) was composed of a protocol of AT and RT in the same session. The intermittent fasting period was 12/12 h. At the end of the experiment, the animals were weighed to obtain the Lee index; heart weight was verified, and tissue samples were collected for further histological analysis. After obtaining the data, the Shapiro-Wilk test was performed, followed by a two-way analysis of variance (ANOVA) with Tukey’s post-test for the variables measured at the end of the experiment.ResultsFor the variables body mass, feed consumption, and the anaerobic threshold, the FC group showed a greater decrease in the Lee index [(0.28 ± 0.00) p < 0.05)] in relation to the other groups. There were no significant alterations (p > 0.05) in relation to heart weight, fractal dimension, and anaerobic threshold (AnT); finally, both the T and the FT groups presented a significant decrease ([T: (277.3 ± 119.3/FT: 310.5 ± 148.8] p < 0.05) in the transverse cross-sectional area of the cardiomyocytes, when compared to the control groups.ConclusionThe practice of concurrent training for a period of 4 weeks precipitated a decrease in the transverse cross-sectional area of the cardiomyocytes of Wistar rats. Furthermore, when combined with intermittent fasting, concurrent training not only led to a reduction in the transverse cross-sectional area of the cardiomyocytes but also resulted in a decrease in body mass compared to the isolated concurrent training model.